التنظيم القانوني لاستثمار البحث العلمي - رحمن ملغيط الجبوري نوفل (Journal of College of Education, 2020)
The investment of scientific research is the basis in the development of societies and the prosperity and improvement of productive and service sectors, where we find the developed world countries interested in scientific research and its outputs and work to put them into practice, as research centers in universities and institutes constitute a huge amount of scientific research output that is not invested correctly, in order to invest and benefit From them it is necessary to support the institutional and academic bodies and find a coordination relationship between the research centers on the one hand and the practical reality on the other hand and make the research activity a simulation of reality and develop appropriate solutions that are consistent with the scientific logic of problems and obstacles In order to achieve this, it requires the legislator to work on setting up a mechanism according to the issuance of a special law in which it specifies the method of investing scientific research and developing research centers, and specifies the bodies responsible for monitoring the investment of scientific research outputs and working to link reality to research activity, and this requires learning about what an investment Scientific research and setting requirements for this investment that make it a real return on all levels in an organized and disciplined manner.